If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(t + 1) = 6 + -1 Reorder the terms: 4(1 + t) = 6 + -1 (1 * 4 + t * 4) = 6 + -1 (4 + 4t) = 6 + -1 Combine like terms: 6 + -1 = 5 4 + 4t = 5 Solving 4 + 4t = 5 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + 4t = 5 + -4 Combine like terms: 4 + -4 = 0 0 + 4t = 5 + -4 4t = 5 + -4 Combine like terms: 5 + -4 = 1 4t = 1 Divide each side by '4'. t = 0.25 Simplifying t = 0.25
| (x+7)2=100 | | -64=-8v | | 18-4x+6=x+9 | | S-15=-15 | | 2x-7x+62=3x+38 | | P=2(pi)r+2x | | 7x-7y=49whatisx | | 8x+9x-3x=52+4 | | (3x-2)/5=(2x-1)/4 | | 2x/3+y/5=0 | | c-8=-17 | | -9d=36 | | 2(x+5)=9x+2-7x+8 | | -(x-6)-6x=-8x+3(-x-6) | | 9x+3=2x+52 | | A+2b/4+4a | | 5(x+4)=2x+29 | | 2q^2+75/2=-20q | | x^4+x=1 | | -8+t=-6 | | X^2=3X-4 | | 4x^5/6x^-3 | | -4(k-1)=10-6k | | 4x^5/6x-3 | | 0=-10x^2+3500x-66000 | | 2d^2+4d-13=0 | | 3=11+4n | | 4x(-2)=12 | | log(6)(x)-log(6)(x+1)=2 | | 14x+3=0 | | y-0.2=0.6(y+3) | | (7x^2+5x/x^2+1)-(5x/x^2-6)=0 |